Digital finance and climate risk information disclosure - Hang Ren; Jianzhong Huang; Jinxin Ren (PLoS ONE, 2026)
Under the dual drivers of China’s “Dual Carbon” goals (carbon peaking and carbon neutrality) and the digital technology revolution, the strategic value of corporate climate risk information disclosure has become increasingly prominent. Against this backdrop, this paper systematically explores the relationship between digital finance development and corporate climate risk disclosure using a sample of Chinese A-share listed firms. The research demonstrates that digital finance development significantly promotes corporate climate risk disclosure, a conclusion that remains valid after multiple robustness tests. The study also reveals that digital finance drives climate risk disclosure through alleviating financing constraints, strengthening environmental responsibility, and enhancing reputational incentives. Further analysis indicates that institutional pressure positively moderates the relationship between digital finance and corporate climate risk disclosure; moreover, the impact of digital finance on corporate climate risk disclosure exhibits significant heterogeneity depending on regional factors (rule of law environments and the supply level of digital economy policies), and corporate characteristics (top management backgrounds, lifecycle stages, and equity nature). These findings provide theoretical references and empirical support for balancing digital finance innovation and climate risk governance.